Towards identifying and security festures of graphical password in knowledge based authentication technique - Muhammad Daniel Hafiz Abdullah, 1978-, author; Abdul Hanan Abdullah, author; Norafida Ithnin, author; Hazinah Kutty Mammi, author; Asia Modelling Symposium (2008 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2008)
PRZSL